Chloride penetration resistance in sound and micro-cracked concretes through different experimental techniques. (8th August 2022) - Russo, Nicoletta; Gastaldi, Matteo; Schiavi, Luca; Strini, Alberto; Lollini, Federica
Highlights: Micro-cracks, induced by mechanical loading, were characterized in width and depth. Sound and micro-cracked specimens were subject to pure diffusion of chloride ions. Chloride diffusion coefficient was evaluated via colorimetric and titration methods. In uncracked conditions good correlation subsisted between the two methods. The effect of micro-cracks resulted more pronounced in more impervious concretes. Abstract: Concrete resistance to chloride penetration is one of the main design parameters for the assessment of reinforced concrete structures durability in chloride-contaminated environments, and it is usually determined through one of the accredited accelerated tests in uncracked configuration. In this study, the resistance to chloride penetration was evaluated on six different concrete types, in uncracked and load-induced micro-cracked configurations, subject to pure diffusion and considering two different analysis techniques, colorimetric and potentiometric titration. Results showed that in uncracked conditions, good correlation subsisted between the diffusion coefficients evaluated through the two techniques. In cracked configuration (micro-cracks 10–75 μm wide and 5–45 mm deep) with both techniques a significant increase in chloride diffusion coefficient was detected for concretes with lower w/c ratio, suggesting that the effect of cracks may be more pronounced for more impervious concretes.